Nanopartículas de dióxido de titânio e avaliação da sua toxicidade no mexilhão dourado (Limnoperna fortunei) - Girardello, Francine (My University, 2016)
Nanotechnology is one of the fastest-growing areas of the actuality. Nanoparticles of titanium dioxide (TiO2-NP) have been widely used in many products and processes in recent years. As consequence, these nanoparticles are release into effluent and wastewater, reaching water compartments. Thus, the evaluation of the biological impact of TiO2-NP becomes of great importance for ecotoxicity. The golden mussel (Limnoperna fortunei) is a freshwater bivalve mollusk often used in biomonitoring, considered target organism for TiO2-NP toxicity in the aquatic environment. In this work, L. fortunei were exposed to TiO2-NP (1, 5, 10 and 50 μg mL-1), which were previously physic-chemically characterized. The toxicological evaluation was performed using the comet assay, micronucleus test, evaluation of oxidative damage to lipids and proteins, assessment of antioxidant defences through the activity of the enzymes superoxide dismutase (Sod) and catalase (Cat) and the protein sulfhydryl content. The TiO2-NP interaction with the haemocytes of golden mussel was evaluated by transmission electron microscopy (TEM). The results showed that TiO2-NP presented average size about 20nm, composed of the anatase and rutile crystalline structures, with surface area of 46.26 m2 g-1. The TiO2-NP solutions of 1, 5, 10 and 50 μg mL-1 used showed low stability with a tendency to form aggregates. The genotoxicity of TiO2-NP was evidenced by DNA damage of L. fortunei after 2 h of exposure and increased after 4 h for all concentrations tested. TiO2-NP was not able to induce micronucleus in haemocytes of golden mussels. The mussels showed an increase in lipid peroxidation levels and carbonylated proteins content after 2 h of exposure to the concentrations of TiO2-NP used. After 4 h of exposure, these values showed no difference compared to control. Sod enzyme activity was decreased after 2 h of exposure for all tested concentrations of TiO2-NP. Cat enzyme activity decreased after 2 h of exposure of the mussels to concentrations of 10 and 50 μg mL-1 TiO2-NP. The non-enzymatic antioxidant defences decreased after 2 h of mussels exposure of all TiO2-NP concentrations used. The mussels showed increased levels of lipid peroxidation and carbonyl proteins after 2 h of exposure to TiO2-NP, showing no similar effects after 4 h of exposure. The enzymatic and non-enzymatic antioxidants defences were depleted after 2 h of TiO2-NP exposure to the mussels. After 4 h of exposure, both enzymatic antioxidant and non-enzymatic defences were restored. As shown by the TEM image analysis, TiO2-NP was internalized by haemocytes of the golden mussel, causing changes in plasmatic membrane structure. The TiO2-NP cause toxicological effects on the golden mussel, which are able to cause genotoxicity and changes in redox metabolism of cells. These results reinforce the care that must be applied to the release of TiO2-NP in the environment due to problems caused by nanoparticles exposure. Furthermore, the data presented demonstrate the potential L. fortunei as biomonitor organism for exposure to nanoparticles.
A nanotecnologia é uma das áreas de maior desenvolvimento da atualidade. Nanopartículas de dióxido de titânio (TiO2-NP) têm sido amplamente utilizadas em diversos produtos e processos nos últimos anos. Como consequência, estas nanopartículas são liberadas em efluentes e águas residuais, atingindo os compartimentos aquáticos. Com isso, a avaliação do impacto biológico das TiO2-NP se torna de grande importância na área de ecotoxicidade. O mexilhão dourado (Limnoperna fortunei) é um molusco bivalve de água doce muito utilizado no biomonitoramento ambiental, considerado organismo alvo para toxicidade de TiO2-NP no ambiente aquático. Neste trabalho, os exemplares do L. fortunei foram expostos às TiO2-NP (1, 5, 10 e 50 μg mL-1), as quais foram previamente caracterizadas físicoquimicamente. A avaliação toxicológica se deu através do ensaio cometa, teste de micronúcleos, avaliação dos danos oxidativo a lipídios e proteínas e avaliação das defesas antioxidantes através da atividade das enzimas superóxido dismutase (Sod) e catalase (Cat) e do conteúdo sulfidril de proteínas. A interação de TiO2-NP com os hemócitos do mexilhão dourado foi avaliada utilizando microscopia eletrônica de transmissão (MET). Os resultados mostraram que as TiO2-NP apresentaram tamanho médio de cerca de 20 nm e são compostas pelas estruturas cristalinas anatase e rutilo, com área superficial de 46,26 m2 g-1. As soluções de 1, 5, 10 e 50 μg mL-1 TiO2-NP utilizadas apresentaram baixa estabilidade com tendência à formação de agregados. A genotoxicidade das TiO2-NP foi evidenciada pelos danos ao DNA do L. fortunei verificados após 2 h de exposição e aumentada após 4 h para todas as concentrações testadas. TiO2-NP não foram capazes de induzir a formação de micronúcleos nos hemócitos do mexilhão dourado. Os mexilhões apresentaram aumento nos níveis de peroxidação lipídica e do conteúdo de proteínas carboniladas após 2 h de exposição às concentrações de TiO2-NP utilizadas. Após 4 h de exposição, esses valores não apresentaram diferença do controle. A atividade da enzima Sod foi diminuída após 2 h de exposição para todas as concentrações testadas de TiO2-NP. A enzima Cat apresentou diminuição na atividade após 2 h de exposição dos mexilhões às concentrações de 10 e 50 μg mL-1 TiO2-NP. As defesas antioxidantes não enzimáticas foram diminuídas após 2 h de exposição dos mexilhões a todas as concentrações de TiO2-NP utilizadas. Após 4 h de exposição, tanto as defesas antioxidantes enzimáticas como as não enzimáticas foram restauradas. Conforme análise das imagens de MET, TiO2-NP foram internalizadas nos hemócitos do mexilhão dourado, ocasionando alterações na estrutura da membrana plasmática. As TiO2-NP causaram efeitos toxicológicos no mexilhão dourado, capazes de causar genotoxicidade e alterações no metabolismo redox nas células dos animais. Estes resultados reforçam os cuidados que devem ser aplicados na liberação das TiO2-NP no ambiente, devido a problemas causados pela exposição às nanopartículas. Além disso, os dados apresentados demonstram o potencial do L. fortunei como organismo biomonitor para a exposição às nanopartículas.
Keywords: Nanotecnologia; Mexilhão dourado; Toxicologia ambiental; Monitoramento biológico; Nanotechnology; Golden mussel; Environmental toxicology; Biological monitoring